Edge-to-edge mitral valve repair for acute mitral valve regurgitation due to papillary muscle rupture: a case report. Issue 1 (6th February 2019) - Papadopoulos, Konstantinos; Chrissoheris, Michael; Nikolaou, Ioulia; Spargias, Konstantinos
Abstract: Background: Papillary muscle (PM) rupture is a devastating mechanical complication of myocardial infarction that leads to cardiogenic shock and death. In this case, we report a patient with acute mitral regurgitation due to PM rupture that was treated successfully with MitraClip. Case summary: An 85-year-old female patient with anterior ST-elevation myocardial infarction complicated with PM rupture and acute severe mitral regurgitation was admitted to our hospital. The patient's surgical risk was considered to be prohibitively high, and was therefore, referred for transcatheter edge-to-edge repair with MitraClip. The procedure was successful, and the patient was discharged home in a stable condition. Discussion: Acute mitral regurgitation due to PM rupture is a mechanical complication of myocardial infarction that should be treated early because of high mortality rates. This case highlights the role of MitraClip in acute mitral regurgitation and acute heart failure as an alternative to surgery method in high-risk patients.